Profile of Leukocytes Differentiation of Silver Pompano (Trachinotus blochii) That Were Fed Using Chicken Feather Meal in Fish Diet Fermented by Bacillus sp. - Ipa, Adha; Lukistyowati, Iesje; Syawal, Henni (Jurnal Perikanan dan Kelautan, 2019)
This research was conducted from July-August 2017. The purpose of the research is to know the effect of adding the chicken feather meal in fish food which was fermented by Bacillus sp. The fermented chicken feather meal was added to the food for adjusting the leukocytes differentiation of Silver Pompano (Trachinotus blochii). The method was an experimental method with a Completely Randomized Design (CRD), one factor with six treatments level. The for 180 fishes. This research used six treatments such as, Kn (negative control): without fermented chicken feather meal by Bacillus sp. in the feed and were not infected by Vibrio alginolyticus, Kp (positive control): without fermented chicken feather meal byBacillus sp. in the feed and were infected by V. alginolyticus, P1-P4 respectively: fermented chicken feather meal by Bacillus sp. in the feed 5%, 10%, 15% and 20%. The collected data is; leukocytestotal, leukocytes differentiation, the average of weight, and survival rate. The results showed that there were a significant effect of adding the fermented chicken feather meal by Bacillus sp.  in the feed to the leukocytes total and leukocytes differentiation of Silver Pompano (Trachinotus blochii). The best treatment was 10% of Bacillus sp.(P2) wich was shown by the80,53x103 cells of leukocytes total, 80,33% of lymphocytes, 9,67 % of monocytes, 10.00 % of Neutrophils, , 5,30 g was the average of weight and100 % of survival rate.